Finding Housing for Resettled Refugees: Accounting for the Tangled Politics of Care in Canada’s Private Refugee Sponsorship Program - Scoles, Cecilia (Université d'Ottawa / University of Ottawa, 2021)
This project examines private sponsors’ experiences with finding and securing housing for privately sponsored refugees (PSR) in Ottawa prior to Operation Syrian Refugee (OSR) (before November 2015); during OSR and the Syrian Refugee Resettlement Initiative (SRRI) (from November 2015 to January 2017); and after the SRRI (from January 2017 to December 2019). Although the PSR program has proved efficient in resettling newcomers in Canada, there has been little recognition of the real cost to sponsors; yet the significant amount of unpaid work these sponsors perform provides the very foundation of the program. I conducted interviews with eight private sponsors and one settlement worker between January and March 2020 to understand the challenges they face, and the social/personal networks on which they rely when navigating the housing market in the city. I also completed a literature review of publicly available information on Immigrant Serving Agency websites in Ottawa to use as a benchmark when comparing sponsorship programs approaches to housing. I demonstrate that sponsors’ deeply caring, but unpaid, voluntary work during their initial housing search often leads to significant overwork. This unpaid caring labour not only represents the very foundation at the basis of the PSR program, but it is also an outcome of the PSR program structure itself. I argue that without more of a structure of support in the PSR program – such as, better guidance or more intervention on the part of the government – sponsors’ feelings of overwork will continue unabated.
Keywords: Private refugee sponsorship; PSR; Syrian Refugee Resettlement Initiative; Care ethics; Ottawa; Housing